Tissue engineered axon‐based "living scaffolds" promote survival of spinal cord motor neurons following peripheral nerve repair. (9th December 2020) - Maggiore, Joseph C.; Burrell, Justin C.; Browne, Kevin D.; Katiyar, Kritika S.; Laimo, Franco A.; Ali, Zarina S.; Kaplan, Hilton M.; Rosen, Joseph M.; Cullen, D. Kacy
Abstract: Peripheral nerve injury (PNI) impacts millions annually, often leaving debilitated patients with minimal repair options to improve functional recovery. Our group has previously developed tissue engineered nerve grafts (TENGs) featuring long, aligned axonal tracts from dorsal root ganglia (DRG) neurons that are fabricated in custom bioreactors using the process of axon "stretch‐growth." We have shown that TENGs effectively serve as "living scaffolds" to promote regeneration across segmental nerve defects by exploiting the newfound mechanism of axon‐facilitated axon regeneration, or "AFAR, " by simultaneously providing haptic and neurotrophic support. To extend this work, the current study investigated the efficacy of living versus nonliving regenerative scaffolds in preserving host sensory and motor neuronal health following nerve repair. Rats were assigned across five groups: naïve, or repair using autograft, nerve guidance tube (NGT) with collagen, NGT + non‐aligned DRG populations in collagen, or TENGs. We found that TENG repairs yielded equivalent regenerative capacity as autograft repairs based on preserved health of host spinal cord motor neurons and acute axonal regeneration, whereas NGT repairs or DRG neurons within an NGT exhibited reduced motor neuron preservation and diminished regenerative capacity. These acute regenerative benefits ultimately resulted in enhanced levels of functional recovery in animals receiving TENGs, at levels matching those attained by autografts. Our findings indicate that TENGs may preserve host spinal cord motor neuron health and regenerative capacity without sacrificing an otherwise uninjured nerve (as in the case of the autograft) and therefore represent a promising alternative strategy for neurosurgical repair following PNI.